PENYULUHAN TENTANG PEMANFAATAN FASILITAS KESEHATAN PADA WARGA KELURAHAN KULIM - Muhammad Firdaus; Shelly Angella; Jihan Syahada; Mey Sarah Azhari (LPPM Universitas Awal Bros, 2021)
Health is one of the basic needs of every human being because healthy people can live, develop and work better. The availability of health care facilities is an important integral part of basic health services for the community and has a very strategic role in accelerating the improvement of public health status and in controlling population growth. Many people in Indonesia still do not use health facilities properly. Lack of knowledge about health facilities can give its own harm to people who are in need of emergency treatment, it is the duty of students to educate the public about this problem. People activities carried out at the home of one the residents who participated in the activity in Kulim Village. As for the results of this activity, almost all residents understand the benefits of health facilities. This activity can also increase public awareness about the use of health facilities.